(untitled) (Південний архів (історичні науки), 2022)
Purpose. Early twentieth century called the defining events of the revival of Ukrainian statehood, in particular the main feature of state formation in this period is the formation and development of the Ukrainian state as the Ukrainian Central Council, Hetmanate of P. Skoropadsky and the Directory of the Ukrainian People’s Republic. The purpose of the article is to reveal the influence of the processes of Ukrainian state formation of 1917–1920 on military construction. Methods. The methodological basis of the study is based on the principles of objectivity and historicism, using methods to analyze historical sources, describe historical events, compare features of military construction in different years and generalize the process of military construction during the Ukrainian state of 1917–1920. Results. It is established that the process of Ukrainian state formation in 1917 and 1920 had a significant effect on military construction. During the Ukrainian Central Rada there was an active process of Ukrainization of the Ukrainian army, but in the end the process of Ukrainization of the army due to the original confidence of the leaders of the Ukrainian Central Rada and, above all, due to neglect of the army. Military construction during the Hetmanate became more progressive in this process, but was not completed due to the constant negative impact on these processes of other states, which feared that the Ukrainian army would grow into a powerful and capable army. Focusing on the processes of military construction during the Directory of the Ukrainian People’s Republic, it should be noted that significant changes in these processes occurred due to the adoption of the Disciplinary Statute and the Law “On Improving the State of the Troops”, gradually collapsed. Conclusions. Considering the peculiarities of military construction during the Ukrainian state formation of 1917–1920, it is established that the process of formation of the Ukrainian army was not completed under any of the ruling regimes. The ruling authorities of each of the studied periods tried to form a strong Ukrainian army, but due to disregard for the needs of the army, personal confidence, intervention of foreign political forces and changes in political course, this task was not fulfilled. In the perspective of the next explorations it is planned to reveal the peculiarities of military construction during the reign of the Western Ukrainian People’s Republic.